The theory of real options as theoretical foundation for the assessment of human capital in organizations - Isabell Welpe; Stephan Lutz; Erich Barthel (Zeitschrift für Personalforschung (ZfP), 2007)
The human capital represented by corporate employees involved in the information and knowledge economy is becoming an increasingly central value-creating factor in global competition. However, in contrast to other value-creating factors, human capital is more difficult to measure, evaluate and manage. Due to human capital's great importance for economic value creation, a series of studies on human capital evaluation have been published during the last few years. This paper discusses why so many traditional evaluation methods are only partly appropriate for categorizing, analyzing and evaluating human capital's special characteristics. In particular, it is difficult for many traditional approaches to integrate notions of flexibility and options with regard to the human capital of companies. Our result shows that the real options theory provides a theoretical framework for the evaluation of human capital and allows a differentiated analysis that, on a qualitative basis, enables investments in uncertainties that are associated with human capital. This theory thus forms the foundation for the quantification of human capital's inherent opportunities and risks. Consequently, this paper provides approaches for the future evaluation of human capital and a conceptual context for empirical studies.
Keywords: 330; human capital; real options; company evaluation; immaterial assets; company value; investment; Humanvermögen; Realoption